Telephone interventions in adherence to receiving the Pap test report: a randomized clinical trial - Ana Izabel Oliveira Nicolau; Thaís Marques Lima; Camila Teixeira Moreira Vasconcelos; Francisco Herlânio Costa Carvalho; Priscila de Souza Aquino; Ana Karina Bezerra Pinheiro (Universidade de São Paulo, 2017)
ABSTRACT Objective: to test the efficacy of the behavioral and educational interventions undertaken by telephone, for women's attendance at the consultation to receive the Pap test report. Method: a randomized clinical trial, with a sample randomized in three groups: telephone call - educational (n=171), telephone call - reminder (n=171) and comparison (n=169). The inclusion criteria were to be of legal age, to have become sexually active, to undertake the preventive examination during the study and to have a mobile or fixed telephone. The educational group received a telephone call involving a script based in the motivational interview and in the Brazilian guidelines. The behavioral group received a telephone call involving a reminder about the consultation. The comparison group received a card with details of when to return for a consultation regarding the results. Results: the women who received one of the interventions had a non-return rate of 7.3% and an increase of 39% (RR CI95%: 1.24-1.55) in the protection against this outcome. In the individual analysis of the interventions, it was evidenced that both are efficacious, as the telephone call - reminder reduces the woman's failure to return to the service by 40% (RR CI95%: 1.25-1.57), while the telephone call - educational does so by 37% (RR CI95%: 1.22-1.54). The rates of non-return were of 6.5% and 8.2%, respectively, as against 33.1% in the comparison group. Conclusion: the interventions tested showed greater efficacy in the educational and behavioral contexts, in relation to the normal attendance, as they motivated the women to return to the service to receive the Pap test report. Clinical trial register: RBR-w3vnc.